Mekanisme Inovatif dalam Membangun Budaya Kepercayaan pada Startup Teknologi - Fadali Rahman; Achmarul Fajar; Aprial Trihandy; Moh Dimas Dwi Prima; Rifki Riyadi (PT. Saha Kreasi Indonesia, 2025)
This study aims to analyze innovative mechanisms in building a trust-based culture within technology startups, which increasingly operate in highly dynamic, uncertain, and competitive digital environments. Trust has become a fundamental element that supports organizational stability, collaboration quality, and the continuity of innovation in startup ecosystems. Through a qualitative descriptive approach and library research method, this study synthesizes findings from previous national and international literature to explore the roles of participatory and authentic leadership, transparent communication systems, flexible and adaptive organizational structures, and the use of collaborative technologies as key mechanisms for fostering trust. The analysis reveals that these mechanisms interact synergistically in creating psychological safety, strengthening team cohesion, and enhancing accountability in digital work processes. Trust-based culture is found to significantly influence innovation capability, team performance, employee retention, and long-term organizational sustainability. The study concludes that building trust through innovative organizational mechanisms is not only a managerial strategy but also a strategic foundation for ensuring the competitiveness and resilience of technology startups in the digital era.